Evaluation of the Policy Arrangement of Street Vendors in Gembong Asih Center Surabaya City - Afifa Ulfa Auliya; Diana Hertati (Department of Public Administration, 2021)
Surabaya, as the second largest metropolitan city, has a long record in overcoming the problem of street vendors who are increasing every year. The existence of irregular street vendors is considered as a barrier in creating a safe, comfortable, orderly, clean layout. The purpose of this study is to describe and analyze the Evaluation of Street Vendor Structuring Policy in Sentra Gembong Asih Surabaya City. The research method uses qualitative descriptive with informant retrieval using purposive sampling techniques. Researchers chose bridgman & davis theory with four focuses: input, process, outputs, outcomes. The results of the study showed that the focus of input, supporting resources are adequate, and human resources are sufficient in number and ability. Focus process, said to be effective, efficient, and has been educated. Focus output, it is said to have not had a successful output in influencing policy goals. Because the existing policy has not met the expectations of traders. Focus outcomes, in the arrangement of traders Gembong Asih the impact received by policy targets has an impact on place and income.